Calculation of Raman Fiber Laser Spectra by a Combination of Shooting Method and Split-Step Fourier Transform Algorithm - Hagen, J.; Engelbrecht, Rainer; Wetzel, O.; Siekiera, Alexander; Schmauß, Bernhard (ECOC September, 2007)
A numerical method for calculation of FWM spectral broadening in Raman fiber lasers is presented. It is based on the steady-state equations and the nonlinear Schrdinger equation. Numerical results are confirmed by measurements.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.calcul